Ripples of mediatization: Social media and the exposure of the pool interview. (March 2016) - Rintel, Sean; Angus, Daniel; Fitzgerald, Richard
Abstract: During the 2011 UK public sector protests, controversy ignited over the "Miliband Loop", an unedited video from a pool interview showing Labour leader Ed Miliband to have provided largely the same answer in response to six questions. The interviewer subsequently complained in a TwitLonger that the incident epitomized the clash of public relations and journalism. In this paper we unpack the practical production of the pool interview as a delamination of the interview-as-lived from the interview-as-media-production-mechanism. We then explore professional and public understanding (or lack thereof) of exposure of this delamination issue and its relation to politics. While the controversy did not directly affect Miliband׳s position as leader, it is clear that the Internet is a dangerous place for the old rules of mediatization. Highlights: Mediatization is a practical collaborative accomplishment of politicians and journalists. Interaction and media production can be laminated or de-laminated. Un-remarked-upon delamination exemplifies collaborative mediatization. Multiple Internet services are medium for exposing and reacting to mediatization. Mediatization ripples out across Internet modalities.